2019
DOI: 10.1038/s41598-019-43416-y
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of HIFU ablation by sonosensitizer-loading liquid fluorocarbon nanoparticles with pre-targeting in a mouse model

Abstract: High intensity focused ultrasound (HIFU) is a noninvasive thermal ablation technique for the treatment of benign and malignant solid masses. To improve the efficacy of HIFU ablation, we developed poly (lactide-co-glycolide) (PLGA) nanoparticles encapsulating perfluoropentane (PFP) and hematoporphyrin monomethyl ether (HMME) as synergistic agents (HMME+PFP/PLGA). Two-step biotin-avidin pre-targeting technique was applied for the HIFU ablation. We further modified the nanoparticles with streptavidin (HMME+PFP/PL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 57 publications
0
23
0
Order By: Relevance
“…Particularly, in more recent decades, NPs have been successfully used in the clinic as effective tools for alternative therapy such as photodynamic therapy (PDT) [ 13 , 14 , 15 ], high-intensity focused ultrasound therapy (HIFU) [ 16 ], photothermal therapy (PPT) [ 17 ] and sonodynamic therapy (SDT) [ 18 , 19 , 20 , 21 ]. The ever-increasing success of these therapies is due to their ability to induce the death of prokaryotic and eukaryotic cells through key cellular mechanisms such as that of induction of NP-mediated reactive oxygen species (ROS) generation [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, in more recent decades, NPs have been successfully used in the clinic as effective tools for alternative therapy such as photodynamic therapy (PDT) [ 13 , 14 , 15 ], high-intensity focused ultrasound therapy (HIFU) [ 16 ], photothermal therapy (PPT) [ 17 ] and sonodynamic therapy (SDT) [ 18 , 19 , 20 , 21 ]. The ever-increasing success of these therapies is due to their ability to induce the death of prokaryotic and eukaryotic cells through key cellular mechanisms such as that of induction of NP-mediated reactive oxygen species (ROS) generation [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is necessary to increase the efficacy of HIFU. Many studies have confirmed that both microbubbles and SDT can improve the efficacy of HIFU [15, 16, 35]. The N 2 O-loaded microbubbles prepared in this study have a smaller particle size, but similar characteristics as ultrasonic microbubble contrast agents.…”
Section: Discussionmentioning
confidence: 59%
“…In addition, microbubbles as an exogenous cavitation nucleus also reduce the tissue cavitation threshold and enhance the cavitation effect of HIFU as it passes through the blood circulation into the tumor tissue [14]. In recent years, studies have indicated that sonodynamic therapy (SDT) can synergistically enhance HIFU treatment efficacy [15, 16]. The interactions between the sonosensitizers and ultrasound produce reactive oxygen species (ROS), including singlet oxygen and hydroxyl radicals, which kill tumor cells and inhibit tumor growth via apoptosis and necrosis [17].…”
Section: Introductionmentioning
confidence: 99%
“…The concept of pre-targeting originates from radionuclide imaging research and has attracted great attention for tumor treatment and imaging (Karacay et al, 2002;Kraeber-Bodere et al, 2015;Zhu, Jain & Baxter, 1998). Ding et al (2019) reported a pre-targeting strategy using technetium 99m -labeled dibenzocyclooctyne derivatives to achieve the imaging of glucose metabolism with a high tumor/blood ratio and tumor/muscle ratio. Zhang et al, (2019) used a two-step biotin-avidin pre-targeting strategy involving poly lactic-co-glycolic acid (PLGA) nanoparticles encapsulating perfluoro-n-pentane (PFP) for high intensity focused ultrasound (HIFU) ablation.…”
Section: Introductionmentioning
confidence: 99%
“…Ding et al (2019) reported a pre-targeting strategy using technetium 99m -labeled dibenzocyclooctyne derivatives to achieve the imaging of glucose metabolism with a high tumor/blood ratio and tumor/muscle ratio. Zhang et al, (2019) used a two-step biotin-avidin pre-targeting strategy involving poly lactic-co-glycolic acid (PLGA) nanoparticles encapsulating perfluoro-n-pentane (PFP) for high intensity focused ultrasound (HIFU) ablation. However, this technology is rarely used in ultrasound molecular imaging and synergistic treatment research.…”
Section: Introductionmentioning
confidence: 99%